Focus on the Controversial Aspects of 64Cu-ATSM in Tumoral Hypoxia Mapping by PET Imaging - Colombié, Mathilde; Gouard, Sébastien; Frindel, Mathieu; Vidal, Aurélien; Chérel, Michel; Kraeber-Bodéré, Françoise; Rousseau, Caroline; Bourgeois, Mickaël (Frontiers in Medicine, 2015)
Mapping tumor hypoxia is a great challenge in Positron Emission Tomography (PET) imaging as the precise functional information of the biological processes is needed for many effective therapeutic strategies. Tumor hypoxia has been widely reported as a poor prognostic indicator and is often associated with tumor aggressiveness, chemo and radio resistance. An accurate diagnosis of hypoxia is a challenge and is crucial for providing accurate treatment for patients’ survival benefits. This challenge has led to the emergence of new and novel PET tracers for the functional and metabolic characterization of tumor hypoxia non-invasively. Among these tracers, copper semicarbazone compound, [64Cu]- diacetyl-bis(N4 methylthiosemicarbazone) (=64Cu-ATSM) has been developed as a tracer for hypoxia imaging. This review focuses on 64Cu-ATSM PET imaging and the concept is presented in two sections. The first section describes its in vitro development and pre-clinical testing and particularly its affinity in different cell lines. The second section describes the controversial reports on its specificity for hypoxia imaging. The review concludes that 64Cu-ATSM - more than a hypoxic tracer, exhibits tracer accumulation in tumor which is linked to the redox potential and reactive oxygen species (ROS). The authors concluded that 64Cu-ATSNM is a marker of over-reduced cell state and thus an indirect marker for hypoxia imaging. The affinity of 64Cu-ATSM for over reduced cells was observed to be a complex phenomenon. And to provide a definitive and convincing mechanism, more in vivo studies are needed to prove the diagnostic utility of 64Cu-ATSM.